Symbol

# Calculator search results

Formula
Solve the equation
Graph
$x - 2 y + 6 = 0$
$x$Intercept
$\left ( - 6 , 0 \right )$
$y$Intercept
$\left ( 0 , 3 \right )$
$x-2y+6 = 0$
$x = 2 y - 6$
 Solve a solution to $x$
$x \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ y } \color{#FF6800}{ + } \color{#FF6800}{ 6 } = 0$
 Move the rest of the expression except $x$ term to the right side and replace the sign 
$x - 2 y \color{#FF6800}{ - } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ y } \right ) = 0 \color{#FF6800}{ - } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ y } \right ) \color{#FF6800}{ - } \color{#FF6800}{ 6 }$
$\color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ y } \color{#FF6800}{ - } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ y } \right ) = 0 - \left ( - 2 y \right ) - 6$
 Organize the expression 
$\color{#FF6800}{ x } = 0 - \left ( - 2 y \right ) - 6$
$x = \color{#FF6800}{ 0 } \color{#FF6800}{ - } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ y } \right ) \color{#FF6800}{ - } \color{#FF6800}{ 6 }$
 Organize the expression 
$x = \color{#FF6800}{ 2 } \color{#FF6800}{ y } \color{#FF6800}{ - } \color{#FF6800}{ 6 }$
$y = \dfrac { 1 } { 2 } x + 3$
 Solve a solution to $y$
$\color{#FF6800}{ x } - 2 y \color{#FF6800}{ + } \color{#FF6800}{ 6 } = 0$
 Move the rest of the expression except $y$ term to the right side and replace the sign 
$- 2 y = 0 \color{#FF6800}{ - } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 6 }$
$- 2 y = \color{#FF6800}{ 0 } \color{#FF6800}{ - } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 6 }$
 Organize the expression 
$- 2 y = \color{#FF6800}{ - } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 6 }$
$\color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ y } = \color{#FF6800}{ - } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 6 }$
 Change the sign of both sides of the equation 
$2 y = x + 6$
$\color{#FF6800}{ 2 } \color{#FF6800}{ y } = \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 6 }$
 Divide both sides by the same number 
$\color{#FF6800}{ y } = \left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 6 } \right ) \color{#FF6800}{ \div } \color{#FF6800}{ 2 }$
$y = \left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 6 } \right ) \color{#FF6800}{ \div } \color{#FF6800}{ 2 }$
 Convert division to multiplication 
$y = \left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 6 } \right ) \color{#FF6800}{ \times } \color{#FF6800}{ \dfrac { 1 } { 2 } }$
$y = \left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 6 } \right ) \color{#FF6800}{ \times } \color{#FF6800}{ \dfrac { 1 } { 2 } }$
 Multiply each term in parentheses by $\dfrac { 1 } { 2 }$
$y = \color{#FF6800}{ \dfrac { 1 } { 2 } } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 6 } \color{#FF6800}{ \times } \color{#FF6800}{ \dfrac { 1 } { 2 } }$
$y = \dfrac { 1 } { 2 } x + \color{#FF6800}{ 6 } \color{#FF6800}{ \times } \color{#FF6800}{ \dfrac { 1 } { 2 } }$
 Calculate the product of rational numbers 
$y = \dfrac { 1 } { 2 } x + \color{#FF6800}{ 3 }$
Have you found the solution you wanted?
Try again
Try more features at Qanda!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture